Maximum likelihood estimation of the equity premium - Avdis, Efstathios; Wachter, Jessica A. (Journal of Financial Economics, 2017)
The equity premium — the expected return on the aggregate stock market less the government bill rate – is of central importance to the portfolio allocation of individuals, to the investment decisions of firms, and to model calibration and testing. This quantity is usually estimated from the sample average excess return. We propose an alternative estimator, based on maximum likelihood, that takes into account information contained in dividends and prices. Applied to the postwar sample, our method leads to an economically significant reduction from 6.4% to 5.1%. Simulation results show that our method produces more reliable estimates under a wide range of specifications.